A two-step trigonometrically fitted semi-implicit hybrid method for solving special second order oscillatory differential equation - Ahmad, Sufia Zulfa; Ismail, Fudziah; Senu, Norazak (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
In this paper, we derived a semi-implicit hybrid method (SIHM) which is a two-step method to solve special second order ordinary differential equations (ODEs). The SIHM which is three-stage and fourth-order is then trigonometrically fitted and denoted by TF-SIHM3(4). The method is constructed using trigonometrically fitted properties instead of using phase-lag and amplification properties. Numerical integration show that TF-SIHM3(4) is more accurate in term of accuracy compared to the existing explicit and implicit methods of the same order.